Human Resources Approach for Optimization of Knowledge Management Implementation: A Case Study at Binus University - Jannana, Nora Saiva; Sulistya, Heru; Qowim, Muhammad; Murfi, Ali (Jurnal Pendidikan Islam, 2021)
Professional human resources view knowledge management as a guarantor of knowledge owned, acquired, and developed together with other people in the organization so that personal knowledge can become organizational knowledge that can contribute to organizational performance. This study aims to analyze the optimization of the implementation of knowledge management at Bina Nusantara University to approach human resources. This approach is carried out to gain commitment and at the same time increase the competence of human resources in using knowledge management. This study uses a qualitative research method with the type of case study. The research results at Bina Nusantara University show that the resource approach focuses on empowering stakeholders, managing perceptions, developing individual competencies and commitments, and appreciating all achievements. This human resource approach is grouped into students, alumni, and parents. Second, industry, business people, and the community. Third, faculty members, and fourth, staff. This research contributes to a deep understanding of the human resource approach for optimizing knowledge management in higher education.